A Rare Cause of Abdominal Pain - Li, Kathleen S (The Royal College of Surgeons of England, 2007)
Pacemaker migration is a rare, but important, complication of pacemaker insertion mainly documented in children. We report the case of a 60-year-old woman who was admitted with right iliac fossa pain thought to be caused by appendicitis. She was noted to have both an epicardial and endocardial pacemaker in situ. Imaging and laparoscopy revealed migration of the epicardial pacemaker to the right iliac fossa. We describe the possible mechanisms of pacemaker migration.